POSTOPERATIVE THREE-DIMENSIONAL CONFORMAL RADIOTHERAPY IN THE PATIENT WITH A SIGNIFICANT CARDIOVASCULAR RISK: A CASE REPORT - Radić, Milica S; Popovic, Aleksandar; Krasic, Katarina; Jovic, Andrija; Conic, Irena; Cvetanovic, Ana; Petkovic, Ivan (Acta medicae Medianae, 2025)
Radiotherapy of breast cancer represents an essential component in the overall multidisciplinary breast cancer treatment. Considering the satisfactory results of the application of the multimodal treatment as well as its role in the decrease in the mortality rate of breast cancer patients, the focus has shifted towards monitoring acute as well as chronic complications occurring as a consequence of oncological treatment, intending to preserve the patient’s quality of life. Complications are numerous and vary from the local ones (dermatitis) to more serious forms including dysfunctions of the cardiovascular system. The application of 3D radiotherapy on the patient in this case report as the most used method in our centre points to its low acute toxic effect, while the observed negative effects in the high-risk patient were removed, which resulted in satisfactory therapeutic effects despite the limited technical equipment of the centre.